George Ball : - Bill, James A. (Yale University Press, 1997)
Bill has examined one diplomat's career in order "to uncover the essence of the American foreign policymaking system and to develop a model of statecraft for the twenty-first century." A string of challenges drew Ball's attention, from his work on European unity with French economist Jean Monnet, to the Congo and Vietnam, to the Cuban missile crisis, civil war in Cyprus, and unending tension and bloodshed in the Middle East. Ball's career stands as an exemplar of what Bill labels phronesis (a form of prudence that balances "passion, proportion, and responsibility") and as an essential alternative to the realpolitik of which Henry Kissinger is perhaps the most obvious proponent